T cell mediated satellite cell function: implications for age-associated changes in skeletal muscle regeneration - Dumke, Breanna R., author; Lees, Simon J., advisor; Gotshall, Robert W., advisor; Frye, Melinda A., committee member (Colorado State University. Libraries, 2010)
Sarcopenia is an age-associated loss of skeletal muscle mass and strength. Recent evidence suggests that an age-associated loss of muscle precursor cell (MPC) functionality contributes to sarcopenia. Current research also suggests that T cells of the immune system may influence skeletal muscle repair via signaling with MPCs. The objective of the present study was to examine the influence of activated T cells on MPCs. MPCs were collected from the gastrocnemius and plantaris from 3-mo-old (young) and 32-mo-old (old) animals. Splenic T cells were also harvested using anti-CD3 Dynabead isolation. T cells were activated for 48 hours with co-stimulation of 100 IU/ml Interleukin-2 (IL-2) and 5 ug/ml of anti-CD28. Co-stimulation increased 5-bromo-2'-deoxyuridine (BrdU) incorporation (proliferation) of T cells from 13.382% (SEM=4.55, n=5) in control to 64.77% (SEM= 6.02, n=5). Additionally, T cell cytokines increased MPC proliferation by 23.98% (SEM=5.69, n=4) in young MPCs but decreased by 1.58% (SEM=4.09, n=4) in old MPCs. T cell cytokines were also found to be chemoattractant. Young MPCs migrated at a rate of 1.36 (SEM=0.56, n=4) with T cell cytokines. Old MPCs, however, did not migrate with T cell cytokines -0.05 (SEM= 0.214, n=4). These data suggest that T cells may play a critical role in mediating MPC function. Furthermore, aging may alter T cell-induced MPC function. These findings have implications for developing strategies aimed at increasing MPC proliferation and the regenerative capacity of aged skeletal muscle.
Keywords: T cell; skeletal muscle; satellite cell; proliferation; migration; conditioned media; Muscles -- Diseases; Muscles -- Regeneration; T cells -- Therapeutic use; Muscles -- Diseases